Low-carbon ceramic prepared by pre-dissolving and activating iron tailings and preparation method of low-carbon ceramic
The low-carbon ceramic process prepared by pre-soluble activation of iron tailings has solved the problems of high CO2 emissions and resource waste in traditional ceramic production, and achieved the effect of low-temperature preparation, low energy consumption and efficient utilization of industrial waste.
Patent Information
- Application Number
- CN202510104116.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-04-11
AI Technical Summary
The production of traditional ceramics consumes a large amount of natural resources and fuel, resulting in high CO2 emissions and it is difficult to effectively utilize industrial solid waste.
The low-carbon ceramic process prepared by pre-soluble activation of iron tailings is used to mix iron tailings powder, corrective materials, alkali triggers and water in proportion to form a pre-soluble slurry, and mold and cure under low temperature conditions, and finally calcined in a low-temperature kiln to make a ceramic product.
The preparation of ceramics under low temperature conditions is achieved, which significantly reduces energy consumption and CO2 emissions, enables a large amount of industrial solid waste to be used, and the process is simple, so the mold is not easily damaged.
Smart Images

Figure CN119797890A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic materials, and in particular to a low-carbon ceramic prepared by pre-dissolving and activating iron tailings and a preparation method thereof. Background Art
[0002] The traditional ceramic production process consumes a lot of natural resources and fuels, and emits a lot of CO2. It is a high resource consumption, high energy consumption and high CO2 emission industry. The ceramic tile industry alone consumed about 50 million tons of standard coal (coal equivalent, referred to as ce) in 2020, with a fuel consumption of about 5.7kgce per square meter, and about 3kgCO2 per kilogram of standard coal. As a high CO2 emission industry, the ceramic industry is also facing great pressure to reduce carbon emissions.
[0003] In February 2022, the "Implementation Guidelines for Energy Saving and Carbon Reduction in Key Areas of High-Energy Consumption Industries (2022 Edition)" was released, of which Appendix 13 is the "Implementation Guidelines for Energy Saving and Carbon Reduction in the Building and Sanitary Ceramics Industries", which proposes to accelerate the research and development and promotion of "green, low-carbon functional building ceramics preparation technology", including "low-temperature fast firing process technology for ceramic tiles (boards)".
[0004] In November 2022, the "Carbon Peak Implementation Plan for the Building Materials Industry" was released, which clearly pointed out that the industrialization of green and low-carbon key technologies in the building materials industry must achieve major breakthroughs, the level of raw material substitution must be greatly improved, and a green, low-carbon and circular development industrial system must be basically established. The ceramic industry is listed as a key industry for carbon reduction.
[0005] Therefore, researching and developing low-carbon preparation methods for ceramics is fully in line with national industrial policies and has important social significance and ecological and environmental benefits.
[0006] Geopolymer is a new type of cementitious material. It is a polysilicate cementitious material with a three-dimensional spatial network structure composed of [SiO4] and [AlO4] tetrahedral structural units alternately bonded by shared oxygen. The biggest advantage of geopolymer is that in addition to using natural minerals containing aluminosilicate substances (such as metakaolin), it can also use a large amount of industrial solid waste (such as fly ash, slag, steel slag, red mud and various tailings, etc.) as the main material. It is formed by the action of alkaline activators at room temperature or slightly higher temperature through geopolymer reaction. In the preparation process of geopolymer, a large amount of industrial solid waste can be used, and there is no direct emission of CO2 or NOx. Therefore, geopolymer is a new type of low-carbon, green cementitious material.
[0007] Due to the unique molecular structure of geopolymers, their performance is far superior to traditional silicate cement-based materials, especially in terms of mechanical properties, chemical corrosion resistance, heat resistance and fixation of heavy metals.
[0008] When studying the excellent heat resistance of geopolymers, it was found that the products formed by geopolymers at room temperature or slightly above room temperature will transform at high temperatures to form new minerals, such as nepheline, pyroxene, leucite, cordierite and other aluminosilicate minerals, which are the main components of ceramics. Some scholars call it ceramic transformation. The ceramic transformation temperature in geopolymers is much lower than the calcination temperature of traditional ceramics. Therefore, ceramic materials can be formed at a lower temperature. In addition, the preparation process of geopolymers is much simpler than the preparation process of green bodies in traditional ceramics, so that the production process consumes less energy. The present invention is based on this principle and proposes to use geopolymers to prepare low-carbon ceramics.
[0009] my country is a mining and steel country with a huge amount of iron tailings and metallurgical waste slag. Its storage has caused serious environmental pollution, and it is urgent to seek new ways of resource utilization. In recent years, a number of policies have been promulgated in succession to encourage the development of resource utilization technology for industrial solid waste. In the traditional ceramic production method, only a very small amount of industrial solid waste can be used, while the ceramic preparation method proposed in the present invention can make the proportion of industrial solid waste in the ingredients exceed 70%. Therefore, the present invention has significant economic benefits, social benefits and ecological environmental benefits. Summary of the invention
[0010] The purpose of the present invention is to provide a low-carbon ceramic prepared by pre-dissolving and activating iron tailings and a preparation method thereof. The ceramic can be prepared using a large amount of industrial solid waste, and has a simple preparation process, a low calcination temperature, and low energy consumption.
[0011] A low-carbon ceramic prepared by pre-dissolving and activating iron tailings, comprising the following raw materials in parts by weight:
[0012] 50-70 parts of iron tailings powder, 10-30 parts of correction materials, 5-20 parts of alkali activator and 40-100 parts of water.
[0013] As a further technical solution of the present invention, the iron tailings powder is a powdery material formed by grinding waste discharged during the iron ore mining and selection process, and its SiO2+Al2O3 mass percentage is not less than 50%, and the particle size is less than 200 mesh.
[0014] As a further technical solution of the present invention, the corrective material is a mixture of one or more of burnt clay and industrial solid waste.
[0015] As a further technical solution of the present invention, the calcined clay is obtained by calcining one of clay materials such as kaolin, montmorillonite, illite, etc. at 500°C to 800°C.
[0016] As a further technical solution of the present invention, the industrial solid waste is one or a mixture of two or more of fly ash, blast furnace slag, and steel slag, and the industrial solid waste is ground to a specific surface area of 300m 2 / kg or more.
[0017] As a further technical solution of the present invention, the alkaline activator is one or a mixture of two or more of water glass, KOH, NaOH, K2CO3, and Na2CO3.
[0018] Another object of the present invention is to provide a method for preparing a low-carbon ceramic prepared by pre-dissolving and activating an iron tailing as described above, comprising the following steps:
[0019] (1) Mix part of the iron tailings powder, part of the alkali activator and water in proportion, and stir for 6h~12h to form a pre-dissolved slurry;
[0020] (2) Add the remaining iron tailings powder, corrective materials, the remaining alkali excitation and an appropriate amount of water to the pre-dissolved slurry and stir for 3 minutes to 10 minutes to form a mixture;
[0021] (3) Pour the evenly stirred mixture into a mold for molding;
[0022] (4) Curing the formed green body with mold in an environment of room temperature to 100°C for 1d~2d;
[0023] (5) After demolding, the green body is cured in an environment of room temperature to 100°C for 2 to 3 days;
[0024] (6) glazing the cured body;
[0025] (7) Drying the green body in an environment of 50°C to 100°C;
[0026] (8) Place the dried green body in a kiln and slowly heat it to the calcination temperature for 2h~8h;
[0027] (9) Slowly cool to room temperature to obtain a ceramic product.
[0028] As a further technical solution of the present invention, the forming is one of compression forming, casting forming and vibration forming, and the mold used for the forming is one of a steel mold, a plastic mold and a fiberglass mold.
[0029] As a further technical solution of the present invention, the glazing is spraying ceramic glaze on the cured green body. For polished ceramic products, glazing is not required.
[0030] As a further technical solution of the present invention, the kiln is one of an electric furnace, a tunnel kiln, a roller kiln, a bell kiln and a drawer kiln.
[0031] As a further technical solution of the present invention, the calcination is carried out at a temperature of 800°C to 1200°C.
[0032] Beneficial effects achieved by the present invention:
[0033] A large amount of industrial solid waste can be used, such as iron tailings, fly ash, blast furnace slag, steel slag, etc. The proportion of industrial solid waste can reach more than 70%. No plaster mold is required, steel mold, plastic mold, fiberglass mold can be used, and the mold is not easy to break. The molding is simple, no waste gypsum treatment is required, low energy consumption, and low CO2 emissions. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 The present invention is a flow chart of a method for preparing low-carbon ceramics by pre-dissolving and activating iron tailings according to an embodiment of the present invention. DETAILED DESCRIPTION
[0035] The technical solution of the present invention is described in detail below in conjunction with the specific drawings.
[0036] The sources of some experimental materials of the embodiments of the present invention are as follows:
[0037] 1) Iron tailings: taken from the iron tailings in Sijiaying, Luan County, and its chemical composition is shown in Table 1;
[0038] Table 1 Chemical composition of iron tailings
[0039]
[0040] 2) Fly ash: Class I fly ash purchased from Lingshou County Power Plant in Shijiazhuang City, its chemical composition is shown in Table 2;
[0041] Table 2 Chemical composition of fly ash
[0042]
[0043] 3) Blast furnace slag powder: S95 grade ore powder purchased from Henan Yuanheng Environmental Protection Engineering Co., Ltd., the chemical composition of which is shown in Table 3;
[0044] Table 3 Chemical composition of blast furnace slag powder
[0045]
[0046] 4) Calcined kaolin: purchased from Lingshou County, Shijiazhuang City, Hebei Province, with a median particle size D50 of 0.924 μm. Its chemical composition is shown in Table 4.
[0047] Table 4 Chemical composition of calcined kaolin
[0048]
[0049] 5) Alkali activator: Analytical grade sodium hydroxide, purchased from Tianjin Yongda Chemical Reagent Co., Ltd.
[0050] The embodiment of the present invention provides a low-carbon ceramic prepared by pre-dissolving and activating iron tailings, which comprises the following raw materials in parts by weight:
[0051] 50-70 parts of iron tailings powder, 10-30 parts of correction materials, 5-20 parts of alkali activator and 40-100 parts of water.
[0052] In this embodiment, the iron tailings powder is a powdery material formed by grinding waste discharged during the iron ore mining and selection process, and its SiO2+Al2O3 mass percentage is not less than 50%, and the particle size is less than 200 mesh.
[0053] In this embodiment, the corrective material is one or a mixture of two or more of burnt clay and industrial solid waste.
[0054] In this embodiment, the calcined clay is obtained by calcining one of clay materials such as kaolin, montmorillonite, illite, etc. at 500° C. to 800° C.
[0055] In this embodiment, the industrial solid waste is one or a mixture of fly ash, blast furnace slag, steel slag, and the industrial solid waste is ground to a specific surface area of 300m 2 / kg or more.
[0056] In this embodiment, the alkaline activator is one or a mixture of two or more of water glass, KOH, NaOH, K2CO3, and Na2CO3.
[0057] See also Figure 1 Another object of the present invention is to provide a method for preparing a low-carbon ceramic prepared by pre-dissolving and activating an iron tailing as described above, comprising the following steps:
[0058] (1) Mix part of the iron tailings powder, part of the alkali activator and water in proportion, and stir for 6h~12h to form a pre-dissolved slurry;
[0059] (2) Add the remaining iron tailings powder, corrective materials, the remaining alkali excitation and an appropriate amount of water to the pre-dissolved slurry and stir for 3 minutes to 10 minutes to form a mixture;
[0060] (3) Pour the evenly stirred mixture into a mold for molding;
[0061] (4) Curing the formed green body with mold in an environment of room temperature to 100°C for 1d~2d;
[0062] (5) After demolding, the green body is cured in an environment of room temperature to 100°C for 2 to 3 days;
[0063] (6) glazing the cured body;
[0064] (7) Drying the green body in an environment of 50°C to 100°C;
[0065] (8) Place the dried green body in a kiln and slowly heat it to the calcination temperature for 2h~8h;
[0066] (9) Slowly cool to room temperature to obtain a ceramic product.
[0067] In this embodiment, the forming is one of pressing forming, casting forming and vibration forming, and the mold used for the forming is one of a steel mold, a plastic mold and a fiberglass mold.
[0068] In this embodiment, the glazing is spraying ceramic glaze on the cured green body. For polished ceramic products, glazing is not required.
[0069] In this embodiment, the kiln is one of an electric furnace, a tunnel kiln, a roller kiln, a bell kiln and a drawer kiln.
[0070] In this embodiment, the calcination is carried out at a temperature of 800°C to 1200°C.
[0071] Example 1. Using iron tailing powder as the main raw material, blast furnace slag powder as the correction material, NaOH as the alkaline activator, 60 parts of iron tailing powder, 40 parts of blast furnace slag powder, 10 parts of NaOH, and 100 parts of water, ceramics were prepared. 30 parts of iron tailing powder were mixed with 8 parts of NaOH and 80 parts of water, and stirred at 80 ° C for 8 hours to form a pre-dissolved slurry. The remaining iron tailing powder, blast furnace slag powder, NaOH and water were added to the pre-dissolved slurry and stirred for 5 minutes. The stirred slurry was poured into a steel mold, allowed to stand for 1 day in a 60 ° C environment, and then demolded. The demolded body was allowed to stand for 2 days in a 50 ° C environment, then glazed, and then dried in an 80 ° C environment. The dried body was placed in an electric furnace and slowly heated to 850 ° C, kept warm for 3 hours, and then slowly cooled to room temperature.
[0072] The main properties of the obtained ceramic product are: water absorption rate 0.8%; whiteness 68%; glossiness 87%; color difference 1.6; no cracking after one heat exchange from 180°C to 20°C.
[0073] Example 2. Using iron tailing powder as the main raw material, fly ash as the correction material, NaOH as the alkaline activator, 60 parts of iron tailing powder, 40 parts of fly ash, 12 parts of NaOH, and 80 parts of water were used to prepare ceramics. 30 parts of iron tailing powder were mixed with 10 parts of NaOH and 70 parts of water, and stirred at 80°C for 8h to form a pre-dissolved slurry. The remaining iron tailing powder, blast furnace slag powder, NaOH and water were added to the pre-dissolved slurry and stirred for 5min. The stirred slurry was poured into a steel mold, allowed to stand for 1d in an 80°C environment, and then demolded. The demolded body was allowed to stand for 3d in a 50°C environment, then glazed, and then dried in an 80°C environment. The dried body was placed in an electric furnace and slowly heated to 1050°C, kept warm for 2h, and then slowly cooled to room temperature.
[0074] The main properties of the obtained ceramic products are: water absorption rate 0.7%; whiteness 66%; glossiness 87%; color difference 1.7; no cracking after one heat exchange from 180°C to 20°C.
[0075] Example 3. Using iron tailing powder as the main raw material, calcined kaolin as the correction material, NaOH as the alkaline activator, ceramics were prepared according to 70 parts of iron tailing powder, 30 parts of calcined kaolin, 10 parts of NaOH, and 100 parts of water. 30 parts of iron tailing powder were mixed with 8 parts of NaOH and 80 parts of water, and stirred at 80°C for 8h to form a pre-dissolved slurry. The remaining iron tailing powder, blast furnace slag powder, NaOH and water were added to the pre-dissolved slurry and stirred for 5min. The stirred slurry was poured into a steel mold, allowed to stand for 1d in a 50°C environment, and then demolded. The demolded body was allowed to stand for 2d in an 80°C environment. The body was placed in an electric furnace and slowly heated to 1000°C, kept warm for 2h, and then slowly cooled to room temperature. Finally, one side of the fired product was polished.
[0076] The main properties of the obtained ceramic products are: 95% of the main areas of the surface have no obvious defects; water absorption rate is 2.1%; destructive strength is 1200N; rupture modulus is 36MPa; wear resistance is 165mm3; no cracks or peeling after antifreeze test.
[0077] It should be noted that, in this article, the term "comprises" or any other variant thereof is intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of more restrictions, an element defined by the sentence "comprises a ..." does not exclude the existence of other identical elements in the process, method, article or device including the element.
[0078] The above are only preferred embodiments of the present invention, and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A low-carbon ceramic prepared by pre-dissolving and activating iron tailings, characterized in that: By weight, it includes the following raw materials: 50-70 parts of iron tailings powder, 10-30 parts of correction materials, 5-20 parts of alkali activator and 40-100 parts of water.
2. The low-carbon ceramic prepared by pre-dissolving and activating iron tailings according to claim 1, characterized in that: The iron tailings powder is a powdery material formed by grinding waste discharged during the iron ore mining and selection process, and its SiO2+Al2O3 mass percentage is not less than 50%, and the particle size is less than 200 mesh.
3. The low-carbon ceramic prepared by pre-dissolving and activating iron tailings according to claim 1, characterized in that: The corrective material is one or a mixture of two or more of burnt clay and industrial solid waste.
4. The low-carbon ceramic prepared by pre-dissolving and activating iron tailings according to claim 3, characterized in that: The calcined clay is one of kaolin, montmorillonite and illite obtained by calcining at 500°C to 800°C.
5. The low-carbon ceramic prepared by pre-dissolving and activating iron tailings according to claim 3, characterized in that: The industrial solid waste is one or a mixture of two or more of fly ash, blast furnace slag, and steel slag, and the industrial solid waste is ground to a specific surface area of 300m 2 / kg or more.
6. The low-carbon ceramic prepared by pre-dissolving and activating iron tailings according to claim 1, characterized in that: The alkaline activator is one or a mixture of two or more of water glass, KOH, NaOH, K2CO3, and Na2CO3.
7. A method for preparing low-carbon ceramics prepared by pre-dissolving and activating iron tailings as claimed in claim 1, characterized in that: The following steps are involved: (1) Mix part of the iron tailings powder, part of the alkali activator and water in proportion, and stir for 6h~12h to form a pre-dissolved slurry; (2) Add the remaining iron tailings powder, corrective materials, the remaining alkali excitation and an appropriate amount of water to the pre-dissolved slurry and stir for 3 minutes to 10 minutes to form a mixture; (3) Pour the evenly stirred mixture into a mold for molding; (4) Curing the formed green body with mold in an environment of room temperature to 100°C for 1d~2d; (5) After demolding, the green body is cured in an environment of room temperature to 100°C for 2 to 3 days; (6) glazing the cured body; (7) Drying the green body in an environment of 50°C to 100°C; (8) Place the dried green body in a kiln and slowly heat it to the calcination temperature for 2h~8h; (9) Slowly cool to room temperature to obtain a ceramic product.
8. The method for preparing low-carbon ceramics prepared by pre-dissolving and activating iron tailings according to claim 7, characterized in that: The molding is one of compression molding, casting molding and vibration molding, and the mold used for the molding is one of a steel mold, a plastic mold and a fiberglass mold.
9. The method for preparing low-carbon ceramics prepared by pre-dissolving and activating iron tailings according to claim 7, characterized in that: The kiln is one of an electric furnace, a tunnel kiln, a roller kiln, a bell kiln and a drawer kiln.
10. The method for preparing low-carbon ceramics prepared by pre-dissolving and activating iron tailings according to claim 7, characterized in that: The calcination is carried out at a temperature of 800°C to 1200°C.